Effect of cerebral oxygen saturation monitoring in patients undergoing superficial temporal anterior-middle cerebral artery anastomosis for ischemic Moyamoya disease: a prospective cohort study - Chen, Xuanling; Qin, Xuewei; Wang, Jing; Wang, Rong; Guo, Xiangyang; Yao, Lan (Frontiers in Neurology, 2023)
Objective: Regional cerebral oxygen saturation (rSO 2 ) is linked with blood pressure. This study evaluated the influence of perioperative rSO 2 monitoring on the prognosis of ischemic moyamoya disease (MMD) patients undergoing anastomosis surgery.In this prospective cohort, patients with unilateral ischemic MMD of Suzuki stage ≥ 3 were included. The decision of rSO2 was made by the clinician and the patient. The rSO 2 group maintained intraoperative rSO 2 levels through modulation of blood pressure, inhaled oxygen concentration, carbon dioxide in arterial blood, and red blood cell transfusion. The non-rSO 2 group used conventional anesthesia practices.Perioperative mean arterial pressure (MAP), rSO 2 values, neurological complications, and postoperative results were assessed.Results: A total of 75 eligible patients were categorized into an rSO 2 monitoring group (n=30) and a non-rSO 2 monitoring group (n=45). For the rSO 2 group, the preoperative rSO 2 was significantly lower on the affected side (P<0.05). After anastomosis, this value notably increased (P=0.01). A moderate relationship was observed between perioperative rSO 2 and MAP before, during, and after surgery, with correlation coefficients (r) of 0.536, 0.502, and 0.592 (P<0.05). Post-surgery MAP levels differed between the groups, with the rSO 2 group showing decreased levels compared to presurgery and the non-rOS 2 group displaying elevated levels. Notably, the rSO 2 group reported shorter hospitalizations and decreased neurological complications. Patients with hypertension history found postoperative MAP influencing hospital stay duration.Perioperative rSO 2 surveillance enhanced cerebral perfusion and minimized postoperative complications in ischemic MMD patients.